Второе рождение материалов - Агабальянц Эдуард Гаспарович (Наукова думка, 1983)
Экземпляры: Ф22 (20210119) / Инвентарный номер: 9174 / Цена: 0.25 / Сис.шифр: 20.1 / Авт.знак: А 23 / ГРНТИ: 87.24 / ББК: 20.1